Pengaruh Penggunaan Metode Visual, Auditori, Kinestetik, Taktil (VAKT) Terhadap Kemampuan Membaca Permulaan Peserta Didik Tunagrahita Ringan Kelas IVC di SLB Negeri Sragen - Afifah Aulia; Selvia Fitri Qustimah; Umi Nasita; Mohammad Anwar; Mardani Mardani (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
This study is based on the ability of children with mild mental retardation who can still develop their reading skills, but cognitive barriers in children with mental retardation cause learning barriers. This study uses the Visual, Auditory, Kinesthetic, and Tactile (VAKT) learning method. The subjects of this study were 3 fourth-grade students with Mental Retardation and were conducted at SLB Negeri Sragen. The research method used was Classroom Action Research (CAR) for 2 cycles. The results showed that the subject's ability in the pre-cycle was 33%, which means that the subject had not yet achieved the specified success criteria. In cycle 1, the average achievement of ability reached 58%, which still did not reach the success criteria of 65%. In cycle II, the results were obtained for early reading ability with an average of 77%, exceeding the success criteria. Based on the results of the data analysis, it can be concluded that there is a significant influence in the use of the VAKT Method on improving the early reading ability of fourth-grade students with mild mental retardation at SLB Negeri Sragen.